The dragon network : inside stories of the most successful Chinese family businesses - Susanto, A. B., 1950-; Susanto, Patricia (New York : Wiley/Bloomberg Press, 2013)
What's driving the burgeoning global Chinese family businesses? Chinese family businesses are the driving force behind Asia's economic prosperity. As the world becomes more global they have had to adapt to the new environment. This timely book draws on an extensive regional survey to reveal the key players and the strategies that will drive their success going forward. The book discusses and analyzes the business life and achievements of some prominent overseas Chinese family businesses in Asia and reveals their life philosophies, their business journey, and their family role in business.
Includes bibliographical references and index.
Keywords: Family-owned business enterprises -- Management; Chinese -- Foreign countries; Family-owned business enterprises -- History; Family corporations -- Management; China -- Economic conditions